Men of Kastom and the Customs of Men: Status, Legitimacy and Persistent Values in Lihir, Papua New Guinea - Bainton, Nicholas A. (The Australian journal of anthropology, 2008)
The changing nature of Lihirian masculinity in the context of large-scale resource development is characterised by ingenuity, disjuncture and struggles for legitimacy. In this paper, I consider the various ways Lihirian masculinity is challenged and shaped by exogenous influences, how Lihirians appropriate particular aspects of modernity for their own purposes, and the ways in which certain Lihirian men have attempted to redefine masculine ideals according to neoliberal democratic values in their quest to modernise Lihir. This paper draws on fieldwork conducted in the Lihir Islands between 2003 and 2007.